2001
DOI: 10.1590/s0034-70942001000600009
|View full text |Cite
|
Sign up to set email alerts
|

Anestesia subaracnóidea em crianças

Abstract: RESUMO minutos e também pela analgesia não abranger o p ó s -o p e r a t ó r i o . A s c o m p l i c a ç õ e s s ã o a s me s m a s encontradas no paciente adulto, incluindo cefaléia por punção dural e irritação radicular transitória. As indicações são várias: cirurgias de abdômen inferior, genitália, membros inferiores, região perineal e, em alguns casos, até em cirurgias torácicas. Seu emprego tem particular interesse nos recém-nascidos prematuros, pelo risco de apresentarem a apnéia da prematuridade.Conclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…In the present study, we recorded longer duration of analgesia with caudal than spinal group, which is comparable to Blaise and Roy [9] . In agreement with the present study, Williams et al [10] showed that spinal anesthesia is associated with 90 minutes duration of analgesia after spinal approach in children, which limits its use for longer surgeries.…”
Section: Dohi and Seinosupporting
confidence: 87%
“…In the present study, we recorded longer duration of analgesia with caudal than spinal group, which is comparable to Blaise and Roy [9] . In agreement with the present study, Williams et al [10] showed that spinal anesthesia is associated with 90 minutes duration of analgesia after spinal approach in children, which limits its use for longer surgeries.…”
Section: Dohi and Seinosupporting
confidence: 87%